DOUBLE SUBORDINATION: SILENCE AND RESISTANCE IN THE COMMUNICATION OF FEMALE PRISONERS WHO ARE SURVIVORS OF SEXUAL VIOLENCE - Putri Annisa; Eko Hero; Bunga Astini (Jurnal Harkat : Media Komunikasi Gender, 2026)
Abstract. This research aims to identify the factors contributing to communication silence, analyse the psychosocial experiences associated with it, and explore resistance strategies among female inmates who are survivors of sexual violence. Employing a qualitative descriptive approach grounded in Muted Group Theory, the study was conducted at the Class IIA Women's Correctional Facility in Pekanbaru involving three informants through screening questionnaires, in-depth interviews, and observations. The results indicate that silence was associated with internal factors (shame, linguistic gaps, and self-voice devaluation) and external pressures (ridicule, authoritative control, and institutional structural barriers). Communication silence was described alongside psychosocial difficulties, including participants’ reports of physical aggression and substance-based coping. Furthermore, survivors developed resistance strategies through symbolic catharsis and identity transformation as forms of communicative agency. In conclusion, the silence of female inmates is a systemic phenomenon arising from double subordination; however, they maintain the agency to negotiate their traumatic experiences. This study contributes theoretically to the expansion of MGT within correctional institutions and recommends providing private communication spaces to support the trauma recovery of inmates.   Abstrak. Penelitian ini bertujuan untuk mengidentifikasi faktor yang berkontribusi terhadap kebungkaman komunikasi, menganalisis pengalaman psikososial yang berkaitan dengannya, serta mengeksplorasi strategi resistensi pada narapidana perempuan penyintas kekerasan seksual. Menggunakan pendekatan kualitatif dengan kerangka Muted Group Theory, penelitian dilakukan di Lapas Perempuan Kelas IIA Pekanbaru terhadap tiga orang informan melalui kuesioner penyaringan, wawancara mendalam, dan observasi. Hasil penelitian menunjukkan bahwa kebungkaman berkaitan dengan faktor internal seperti perasaan malu, linguistic gap, dan devaluasi suara sendiri, serta faktor eksternal seperti ejekan, kontrol otoritas, dan hambatan struktural institusi. Kebungkaman juga muncul bersamaan dengan kesulitan psikososial, termasuk laporan informan mengenai agresi fisik dan penggunaan zat sebagai mekanisme koping. Strategi resistensi dikembangkan melalui katarsis simbolik dan transformasi identitas sebagai bentuk agensi komunikatif. Kesimpulannya, kebungkaman narapidana merupakan fenomena sistemik akibat subordinasi ganda, namun mereka tetap memiliki agensi untuk menegosiasikan traumanya. Penelitian ini memberikan kontribusi teoretis pada perluasan MGT dalam institusi pemasyarakatan serta merekomendasikan penyediaan ruang komunikasi yang menjamin privasi untuk mendukung pemulihan trauma narapidana.